Assessment of Efficacy and Safety of Dr.Ortho Capsules in Managing Musculoskeletal Disorders: A Phase IV Post-Marketing Surveillance Study (International Journal of Ayurveda and Pharma Research, 2024)
Objectives: This study aimed to evaluate the potential efficacy and safety of Dr. Ortho capsules in managing various musculoskeletal conditions, including knee pain, joint stiffness, arthritis, bulky shoulders, joint inflammation, acute sports injuries, strains, and sprains. Methods: The study was a single centric, open-label, non-randomized, post-marketing surveillance study involving 120 subjects. Subjects were selected based on inclusion and exclusion criteria. The study assessed changes in pain intensity and disability levels after the administration of Dr. Ortho capsules, employing the Visual Analog Scale (VAS) and Oswestry Disability Index (ODI), respectively. Additionally, safety was evaluated through physical examinations, vital sign monitoring, and laboratory safety parameters. Results: The study revealed significant reductions in pain intensity and disability levels among the participants. Pain intensity, as measured by VAS, decreased significantly (p< 0.0001) from a mean score of 4.84 at baseline (day 1) to 0.38 at the end of the study (day 30). Disability levels, indicated by ODI, significantly improved (p